2004
DOI: 10.1074/jbc.m309325200
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Stress Activates Glycogen Synthase Kinase 3β-mediated Apoptosis of Renal Medullary Interstitial Cells, Suppressing an NFκB-driven Cyclooxygenase-2-dependent Survival Pathway

Abstract: The survival of renal medullary interstitial cells (RMICs) requires their adaptation to rapid shifts in ambient tonicity normally occurring in the renal medulla. Previous studies determined that cyclooxygenase-2 (COX 2) activation is critical for this adaptation. The present studies find that these adaptive mechanisms are dampened by the simultaneous activation of an apoptotic pathway linked to a glycogen synthase kinase 3␤ (GSK 3␤). Inhibition of GSK 3 by LiCl or specific small molecule GSK inhibitors increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 56 publications
6
76
0
Order By: Relevance
“…Moreover, suppression of GSK-3␤ with lithium or more specific inhibitors enhanced the transcriptional activity of NF-B in renal medullary interstitial cells. 60 In contrast, genetic depletion of GSK-3␤ resulted in embryonic fatality with similar pathological features as those produced by gene targeting of IkB kinase-␤, an enzyme critical to NF-B activation, or of the p65 subunit of NF-B itself. 20 These results strongly suggested that GSK-3␤ activates the transcription factor.…”
Section: Inactivation Of Gsk-3␤ Is Associated With Deregulation Of Nf-bmentioning
confidence: 99%
“…Moreover, suppression of GSK-3␤ with lithium or more specific inhibitors enhanced the transcriptional activity of NF-B in renal medullary interstitial cells. 60 In contrast, genetic depletion of GSK-3␤ resulted in embryonic fatality with similar pathological features as those produced by gene targeting of IkB kinase-␤, an enzyme critical to NF-B activation, or of the p65 subunit of NF-B itself. 20 These results strongly suggested that GSK-3␤ activates the transcription factor.…”
Section: Inactivation Of Gsk-3␤ Is Associated With Deregulation Of Nf-bmentioning
confidence: 99%
“…RMICs were transfected with a NFB 3ϫ-luc reporter 52 or a mouse COX-2 promoter (Ϫ815)-luc reporter 53 with Lipofectamine 2000 (Invitrogen) under conditions recommended by the manufacturer. A ␤-galactosidase reporter gene (Promega) was cotransfected for normalization.…”
Section: Luciferase Reporter Assaysmentioning
confidence: 99%
“…To this end, we selected a lithium compound as a test chemical by the following reasons. First, lithium has been reported to induce COX-2 in vivo (Rao et al, 2005;Kim et al, 2008) and in vitro (Rao et al, 2004), but no detailed analysis has been performed on the pathogenesis of hydronephrosis. Second, lithium is an important therapeutic drug for treatment of mood disorder and Alzheimer's disease (Eldar-Finkelman, 2002;Luna-Medina et al, 2005;Woodgett, 2001) and has been routinely prescribed in a clinical practice.…”
Section: Introductionmentioning
confidence: 99%